PENGARUH KUALITAS AUDIT, DEBT DEFAULT, AUDIT LAG, DAN DISCLOSURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Yasmin Afnan (2020)
This study aims to determine the effect of Audit Quality, Debt Default, Audit Lag, and Disclosure on the Acceptance of Going Concern Audit Opinion. The object of this study are banking companies listed in the IDX in the period 2014-2018. The sampling technique used is purposive sampling method with predetermined criteria. A total of 33 companies were selected as samples. The data used for this research are secondary data derived from annual reports and auditor reports issued by banking companies. The test used in this study is a logistic regression model using SPSS version 20 with a significance level of 5%. The results of the study indicate that audit quality affects the acceptance of Going Concern Audit Opinions with a significance level of 0.002. Debt Default affects the acceptance of Going Concern Audit Opinion with a significance level of 0.001. Audit Lag does not affect the acceptance of the Going Concern Audit Opinion with a significance level of 0.713. Disclosure has no effect on acceptance of Going Concern Audit Opinion with a significance level of 0.985.